Somatonyms of the thematic subgroup of arms in the Northern Samogitian subdialect: ethnoanatomical categorization and expression - Lubienė, Jūratė; Pakalniškienė, Dalia (Baltistica, 2025)
This article presents a study of the thematic subgroup of arms / hands in the Northern Samogitian subdialect based on the Two-level Semantics methodological approach, which allows us to identify the tendencies of the ethnoanatomical categorization of the arm / hand as well as cognitive features of the concept ARMA / HAND.